PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP PENGAMBILAN KEPUTUSAN MASYARAKAT SAMARINDA UNTUK BELI PADA WARUNK UPNORMAL DI SAMARINDA - Br Pelawi, Betsy Even Jelita (EKONOMIA, 2019)
The advancement of information technology has influenced changes in marketing patterns and conventional consumer behavior to become more modern. Electronic Word Of Mouth or E-WOM is an easy and appropriate choice to promote in a company's business because it can be accessed anywhere and makes it easy for its users. This affects consumer behavior, one of which is the consumer's decision to buy.          This study aims to determine the effect of electronic word of mouth on purchasing decisions at Warunk Upnormal branch Samarinda. The research method used in this research is quantitative descriptive, where the data obtained through questionnaires. The sampling technique used in this study is nonprobability sampling with accidental sampling method. The questionnaire was distributed to 60 respondents who were shopping at the Warunk Upnormal branch in Samarinda. Data analysis used in this study is multiple linear analysis.          Based on data analysis, the results showed that: (1) the variables (intensity, valence of opinion, and content) of e-WOM had a positive and significant effect simultaneously on purchasing decisions of 12,436. (2) intensity variables have a positive and significant influence on purchasing decisions of 4,786. (3) variable valence of opinion has a positive and insignificant effect on purchasing decisions of 0.177. (4) Content variables have a positive and significant effect on purchasing decisions of 2,231.